PENGEMBANGAN MEDIA FLAP BOOK MATERI UNDERSTANDING EVERYDAY VOCABULARIES UNTUK SISWA KELAS III SEKOLAH DASAR - Tiara Nabila Faradiva; Andang Firmansyah; Dyoty Auliya Vilda Ghasya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of having good English language skills. Good English language skills in elementary school students can open up a wide range of experiences and knowledge to help them understand the world more broadly. The purpose of this study was to produce a product that can support English language learning through interactive media so that learning becomes more meaningful and contextual. This study used a mixed-method approach with a Research and Development (R&D) design employing the ADDIE model, which was limited to three main stages, namely Analysis, Design, and Development, with a sample of 24 third-grade students from SDS Adicita Mulia selected through purposive sampling. Data were obtained from various sources, including interviews, observations, expert validation results, and product usage response questionnaires from teachers and students, and were analyzed using Likert scale analysis techniques and percentage calculations. The results of the study indicate that the Flap Book media were developed in accordance with students’ needs and the learning outcomes of the Merdeka Curriculum Phase B. These findings are in line with the research objectives and reinforce Piaget’s theory, which states that students aged 7–11 years are in the concrete operational stage and require concrete supporting media in their learning development stage. The main conclusion of this study is that interactive books such as Flap Book are suitable media for the developmental stage and learning styles of students in the concrete operational stage.